Lettering, Marshall Sons and Co. building - Ghosh, Ayan (2023)
Lettering at Marshall Sons and Co., which was an engineering company. It now has offices of the Central Bank of India on its ground floor. Completed in 1906, this was among the first buildings to come up at Ballard Estate, built during the first phase of development. Seen here are pillars of the Ionic order featuring twin volutes as pillar capitals.